PENDIDIKAN FORMAL DAN EKSISTENSI BUDAYA: STUDI ANTROPOLOGI SOSIAL BUDAYA TERHADAP SUKU KAJANG DI DESA TANA TOA - Abdul Hafid; -, Kaharuddin; Lukman Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Since Sir Isaac Newton, positivist ways of knowing have dominated Society with the logic of modernity that makes people assume that science and technology (scientific knowledge) and local knowledge are an antinomy, where one negates the other. This study utilizes Pierre Bourdieu's conceptual-theoretical framework of Habitus, Capital, and Arena to define and analyze, and explain the attitudes of the Kajang Indigenous Community in Tana Toa towards cultural capital and educational institutions and further, how they interpret and view Education as an alternative to maintaining and preserving culture. 14 respondents who are Customary, Religious and Educational figures representing gender subjects determined by Purposive sampling techniques, were included as informants in the study. Our field findings provide strong evidence that the Kajang Community has adequate strategies and adaptation capabilities in maintaining and preserving the existence of their culture, creating a harmonious blend of local and formal knowledge.